Crosstalk Noise Analysis with RLC Coupled Interconnects in VLSI Circuits - B. Obulesu, Dr. P. Sudhakara Rao (International Journal of Control and Automation, 2020)
VLSI begans in the 1970s when complex semiconductor and communication technologies were being developed. The rapid development of VLSI technology has reduced the minimum element size to a quarter of a micron and the switching period in units of peak seconds or fewer. As an outcome, degradation of high speed digital paths due to crosstalk. Crosstalk is a phenomenon in which the logic transmitted on a VLSI or network / cable circuit creates an undesired effect on an adjacent circuit or network / cable due to the capacitive coupling. The decrease of crosstalk in a VLSI connection has become much essential for digital circuits at high level. In this project estimation of crosstalk noise analysis with equally connected RLC interconnect in VLSI circuits is implemented with simulations results in CADENCE TOOLS.